Understanding implementation success: protocol for an in-depth, mixed-methods process evaluation of a cluster randomised controlled trial testing methods to improve detection of Lynch syndrome in Australian hospitals. Issue 6 (15th June 2020) - Morrow, April; Tucker, Katherine M; Shaw, Tim J; Parkinson, Bonny; Abraham, Charles; Wolfenden, Luke; Taylor, Natalie
Abstract : Introduction: In multisite intervention trials, implementation success often varies widely across settings. Process evaluations are crucial to interpreting trial outcomes and understanding contextual factors and causal chains necessary for successful implementation. Lynch syndrome is a hereditary cancer predisposition conferring an increased risk of colorectal, endometrial and other cancer types. Despite systematic screening protocols to identify Lynch syndrome, the condition remains largely underdiagnosed. The Hide and Seek Project ('HaSP') is a cluster randomised controlled trial determining the effectiveness of two approaches to improving Lynch syndrome detection at eight Australian hospital networks. To enhance widespread implementation of optimal Lynch syndrome identification, there is a need to understand not only what works, but also why, in what contexts, and at what costs. Here we describe an in-depth investigation of factors influencing successful implementation of procedures evaluated in the HaSP trial. Methods and analysis: A mixed-methods, theory-driven process evaluation will be undertaken in parallel to the HaSP trial. Data will include: interviews of Implementation Leads and Lynch syndrome stakeholders, pre–post implementation questionnaires, audio analysis of meetings and focus groups, observation of multidisciplinary team meetings, fidelity checklists and project log analysis. Results will be triangulated and coded, drawing on the Theoretical Domains Framework, Consolidated Framework for Implementation Research and Proctor's implementation outcomes. Ethics and dissemination: Use of a theory-based process evaluation will enhance interpretation and generalisability of HaSP trial findings, and contribute to the implementation research field by furthering understanding of the conditions necessary for implementation success. Ethical approval has been granted and results will be disseminated via publications in peer-reviewed journals and conference presentations. At trial completion, key findings will be fed back to sites to enable refinement of intervention strategies, both in the context of Lynch syndrome and for the possible generalisability of intervention components in other genetic and broader clinical specialties. HaSP trial registration number: Australian New Zealand Clinical Trials Registry (Identifier: ACTRN12618001072202). Registered 27 June 2018. http://www.ANZCTR.org.au/ACTRN12618001072202.aspx .